2013
DOI: 10.1002/jgrc.20331
|View full text |Cite
|
Sign up to set email alerts
|

Combining observations and numerical model results to improve estimates of hypoxic volume within the Chesapeake Bay, USA

Abstract: [1] The overall size of the ''dead zone'' within the main stem of the Chesapeake Bay and its tidal tributaries is quantified by the hypoxic volume (HV), the volume of water with dissolved oxygen (DO) less than 2 mg/L. To improve estimates of HV, DO was subsampled from the output of 3-D model hindcasts at times/locations matching the set of [2004][2005] stations monitored by the Chesapeake Bay Program. The resulting station profiles were interpolated to produce bay-wide estimates of HV in a manner consistent wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 59 publications
(99 citation statements)
references
References 46 publications
6
93
0
Order By: Relevance
“…The Estuarine-CarbonBiogeochemistry (ECB) component of the model (Feng et al, 2015) was developed originally from a continental shelf application (Hofmann et al, 2011), using dissolved organic matter cycling similar to that described in Druon et al (2010). With only single phytoplankton and zooplankton classes and only one limiting nutrient (nitrogen), the ECB model is simpler than that employed by the Chesapeake Bay Program (Cerco et al, 2010) but is more complex than simple dissolved-oxygen models that utilize a constant oxygen consumption rate (e.g., Scully, 2010;Bever et al, 2013). ChesROMS-ECB has been previously shown to adequately resolve the spatial and temporal variability of key physical and biological variables such as temperature, salinity, nitrogen, and DO (Feng et al, 2015;Irby et al, 2016).…”
Section: Chesroms-ecbmentioning
confidence: 99%
See 2 more Smart Citations
“…The Estuarine-CarbonBiogeochemistry (ECB) component of the model (Feng et al, 2015) was developed originally from a continental shelf application (Hofmann et al, 2011), using dissolved organic matter cycling similar to that described in Druon et al (2010). With only single phytoplankton and zooplankton classes and only one limiting nutrient (nitrogen), the ECB model is simpler than that employed by the Chesapeake Bay Program (Cerco et al, 2010) but is more complex than simple dissolved-oxygen models that utilize a constant oxygen consumption rate (e.g., Scully, 2010;Bever et al, 2013). ChesROMS-ECB has been previously shown to adequately resolve the spatial and temporal variability of key physical and biological variables such as temperature, salinity, nitrogen, and DO (Feng et al, 2015;Irby et al, 2016).…”
Section: Chesroms-ecbmentioning
confidence: 99%
“…Hypoxic volume is a commonly used metric to quantify the amount of water that experiences a given level of DO concentration over a specific time (e.g., Murphy et al, 2011;Bever et al, 2013). In this study, two metrics related to hypoxic volume are computed: cumulative hypoxic volume (CHV) and hypoxic duration (HD).…”
Section: Dissolved-oxygen Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al, 2015). Bever et al (2013) specifically demonstrated that multiple models of varying complexity are able to generate skillful estimates of hypoxic volume in the bay. Some of these models are being used in the bay to simulate short-term and/or seasonal forecasts of DO conditions.…”
Section: D Irby Et Al: Multiple Modeling Low-oxygen Waters 2013mentioning
confidence: 99%
“…Since the middle of the last century, anthropogenic impacts have dramatically decreased water quality throughout the Chesapeake Bay (Boesch et al, 2001), one of the largest estuaries in North America. Land-use change along with the industrialization and urbanization of the Chesapeake Bay watershed have caused dramatic increases in nutrient inputs to the bay (Kemp et al, 2005), spurring additional primary production and phytoplankton abundance (Harding Jr. and Perry, 1997).…”
Section: Introductionmentioning
confidence: 99%